Development and kinematic analysis of scotch yoke (crank wheel) / Muhammad Afif Zawawi - Zawawi, Muhammad Afif (2022)
The Scotch Yoke Device is a very simple mechanism for converting a slider's linear motion into motility motion and vice versa. A sliding bar, a yoke on the bar with a slot cut out, and a smaller bar connected to the yoke and attached to the slippery bar by a pin via the yoke slot are the components of this device. The smaller bar is pushed to slip up and down within the yoke slot as the bar slides back and forth, creating a motion movement. This motion connection also holds true in reverse; when the pin commences a rotating movement, the slider creates a reciprocal or back and forth movement. In use, the reciprocating portion is directly attached to the sliding bar or yoke through a slot that contacts the spinning part's pin. The motion of the Scotch Yoke Mechanism is such that when driven by an eccentric or crank, the mechanism produces pure simple harmonic motion. These graphs have a perfect wave shape since velocity and acceleration are derivatives of the displacement time curve. Scotch Yoke Mechanism is commonly used in high oil and gas pipeline management valve actuators. Although it is no longer a prevalent metalworking equipment, rudimentary shapers still employ Scotch yokes. [1]